2004
DOI: 10.1177/230949900401200115
|View full text |Cite
|
Sign up to set email alerts
|

A New Clinical Test for Radial Tunnel Syndrome—The Rule-of-Nine Test: A Cadaveric Study

Abstract: The Rule-of-Nine test is proposed as a reliable method of diagnosing radial tunnel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…Additional physical examination tests that have been described include pain with resisted active supination or wrist extension, pain with resisted middle finger extension at the metacarpophalangeal joint, 48,49 and localized tenderness along the path of the PIN. 50 The practitioner should remember, of course, that several of these clinical maneuvers would also provoke pain in the patient with lateral epicondylitis.…”
Section: Radial Tunnel Syndrome (Rts)mentioning
confidence: 99%
“…Additional physical examination tests that have been described include pain with resisted active supination or wrist extension, pain with resisted middle finger extension at the metacarpophalangeal joint, 48,49 and localized tenderness along the path of the PIN. 50 The practitioner should remember, of course, that several of these clinical maneuvers would also provoke pain in the patient with lateral epicondylitis.…”
Section: Radial Tunnel Syndrome (Rts)mentioning
confidence: 99%
“…The point of bifurcation is varied. Studies have shown that it occurs within an area of 3 cm proximal or distal to the elbow and therefore the split is not always in the radial tunnel [14]. The superficial radial nerve is a purely sensory nerve which runs under the brachioradialis in the forearm.…”
Section: Discussionmentioning
confidence: 99%
“…The rule-of-9 test, described by Loh and colleagues 6 and Stanley, 7 consists of drawing a large square box over the anterior aspect of the proximal forearm. This box is further divided into 9 smaller, equal squares.…”
Section: Physical Examinationmentioning
confidence: 99%